Philosophical foundations of tax law / edited by Monica Bhandari. - Bhandari, Monica (Philosophical foundations of law., 2017)
This collection brings together major themes and difficult questions in the philosophical foundations of tax law. It allows the reader to consider how tax systems should move forward in the modern world, with a sound philosophical basis, to provide the practical tax system that the state requires and citizens deserve.